Civil Religion dan Masa Depan Umat Beragama di Indonesia: Mempertemukan Ideologi Keagamaan dan Ideologi Kebangsaan - Irham, Muhammad Aqil (Universitas Islam Negeri Raden Intan Lampung, 2017)
The rise of religious ideological movements and national ideology in Indonesia is still felt today. As a result of that, there are often truth claims that sometimes end in chaos in the public. So to mediate it all requires an independent and neutral view. The view referred to is none other than the existence of a civil religion. Civil religion or